2008
DOI: 10.1063/1.2912011
|View full text |Cite
|
Sign up to set email alerts
|

Modulations of photoinduced magnetoconductance for polymer diodes

Abstract: This study elucidates the magnetoconductance (MC) response of polymer diodes, which can be modulated by photoillumination, varying the composition of the active layer and applying electrical bias. Under illumination, the short-circuit current of polymer diodes with active layers of regioregular poly(3-hexylthiophene) (P3HT) exhibits an MC response of approximately −4.0% in a magnetic field B=1000mT at room temperature. The MC response drastically reverses from negative to positive (−23.0% to 2.0%) as the elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 19 publications
1
3
0
1
Order By: Relevance
“…However, detailed temperature, higher magnetic field, material and thickness dependent study of the MR line-shapes are needed to clarify the effect. This observation is in good agreement with Lee et al, who found similar behavior in light-induced MR response on P3HT/PCBM solar cells [14].…”
supporting
confidence: 93%
“…However, detailed temperature, higher magnetic field, material and thickness dependent study of the MR line-shapes are needed to clarify the effect. This observation is in good agreement with Lee et al, who found similar behavior in light-induced MR response on P3HT/PCBM solar cells [14].…”
supporting
confidence: 93%
“…The MC effect is defined as the ratio of the variation of the current density J induced by applying an external magnetic field B to the current density in the absence of B : MC = [ J ( B ) – J (0)] × 100/ J (0). It has been extensively investigated in organic solids, and it has recently been reported that OSC devices without magnetic electrodes also exhibit the MC effect in both dark and light conditions. , Numerous mechanistic studies on various organic semiconductors have shown that the carrier dynamics of spin-carrying pairs following the spin conservation rule during collisions are crucial for the intrinsic MC effect. Because an external magnetic field depresses the spin mixing in the spin-carrying pairs before the reaction, unless the magnetic field is higher than several tesla, , the product fraction of the spin-selective reaction changes with the field strength. The magnetic field dependence of the MC effect normally saturates in magnetic fields that are high in comparison with the internal magnetic field driving the spin mixing.…”
Section: Introductionmentioning
confidence: 99%
“…It has been extensively investigated in organic solids, 12−16 and it has recently been reported that OSC devices without magnetic electrodes also exhibit the MC effect in both dark and light conditions. 17,18 Numerous mechanistic studies on various organic semiconductors have shown that the carrier dynamics of spin-carrying pairs following the spin conservation rule during collisions are crucial for the intrinsic MC effect. 19−28 Because an external magnetic field depresses the spin mixing in the spin-carrying pairs before the reaction, unless the magnetic field is higher than several tesla, 24,29 the product fraction of the spin-selective reaction changes with the field strength.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature the high-field effect on the photocurrent, and even regular OMAR, is sometimes explained by these reactions of triplet excitons. 34,35 However, most of the calculations on triplet reactions in the literature are focused on single crystals. 13,33,36 We will use the stochastic Liouville equation to study the magnetic-field-dependence of triplet reactions in disordered organic semiconductors.…”
Section: A Basic Conceptsmentioning
confidence: 99%